PWE-184 Prevalence, management and outcomes of patients with coagulopathy following acute non-variceal upper gastrointestinal bleeding. (28th May 2012) - Jairath, V; Kahan, B; Logan, R; Hearnshaw, S; Travis, S; Murphy, M; Palmer, K
Abstract : Introduction: There is increasing interest in optimising transfusion strategies in patients with major haemorrhage. In other models of haemorrhage such as trauma, an endogenous coagulopathy early in the disease course is associated with increased mortality, with subsequent implications for transfusion management. Non-variceal upper gastrointestinal bleeding (NVUGIB) is a leading cause of admission with haemorrhage and for transfusion of blood components. The impact of coagulopathy in this group is poorly characterised. We characterised in patients presenting with NVUGIB 1) the epidemiology of a key marker of coagulopathy, a prolonged International Normalised Ratio (INR) and the association of coagulopathy with patient survival and other key clinical outcomes. Methods: We used data from the 2007 UK national audit of acute upper gastrointestinal bleeding (AUGIB) and the use of blood. We included those patients with endoscopically confirmed NVUGIB and excluded those with documented cirrhosis. Coagulopathy was defined as an INR>1.5. A logistic regression model was used to compare risk adjusted clinical outcomes in those patients with coagulopathy vs those without coagulopathy. Results: An INR at presentation was performed in 61% (2709/4478) of patients with NVUGIB. The prevalence of coagulopathy (INR ≥1.5) was 16.4% (444/2709). Patients with coagulopathy were older, more likely to present with shock (45% vs 36%), have a higher clinical Rockall (4 vs 2), more likely to have high risk stigmata at endoscopy and more likely to be transfused both red blood cells (70% vs 48%) and FFP (35% vs 3%). 8% (220/2709) of all patients who had an INR recorded received FFP transfusion during their admission. In those patients with an INR of Conclusion: An early coagulopathy is prevalent in patients presenting with acute NVUGIB and is independently associated with in-hospital mortality. The wide variation in the use of FFP to correct this suggests clinical uncertainty regarding best practice. Competing interests: None declared.